The complete chloroplast genome sequences of Artemisia gmelinii andArtemisia capillaris (Asteraceae) - Lee, Yun Sun (Mitochondrial DNA B Resour, 2016)
In this study, complete chloroplast sequences of Artemisia gmelinii and Artemisia capillaris (the Asteraceae family), which have been used as herbal medicine in Korea, were characterized by de novo assembly with whole-genome sequence data. The genomes of A. gmelinii and A. capillaris were 151,318 bp and 151,056 bp in length, respectively. Both genomes harbored identical number of annotated genes, such as 80 protein coding genes, 4 rRNA genes and 30 tRNA genes. Phylogenetic tree revealed that both A. gmelinii and A. capillaris were closely grouped with other Artemisia species.